2018
DOI: 10.1080/01913123.2018.1462874
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological effect of bladder outlet obstruction on the urothelium

Abstract: Bladder outlet obstruction (BOO) and associated lower urinary tract symptoms are major urological issues that significantly affect patient's quality of life and may lead to severe complications. The prevalence of both is increasing each year, raising the burden to health system. Therefore, casual and symptomatic treatment should be of great importance. However, management of symptoms is often difficult as their pathophysiology is multifactorial and not well elucidated. Recently urothelium has gathered much att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Pathological tissue remodeling in bladders can be caused by BOO. These alterations include malfunction of urothelium, smooth muscle hypertrophy, and extracellular matrix (ECM) deposition that would result in LUTS, decreased bladder compliance, residual urine, and even dysfunction of the organ 4,5 . ECM accumulation is of great importance in the progression of BOO that can change the biomechanical properties of the bladder, leading to the transition from compensation to decompensation 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathological tissue remodeling in bladders can be caused by BOO. These alterations include malfunction of urothelium, smooth muscle hypertrophy, and extracellular matrix (ECM) deposition that would result in LUTS, decreased bladder compliance, residual urine, and even dysfunction of the organ 4,5 . ECM accumulation is of great importance in the progression of BOO that can change the biomechanical properties of the bladder, leading to the transition from compensation to decompensation 6 …”
Section: Introductionmentioning
confidence: 99%
“…These alterations include malfunction of urothelium, smooth muscle hypertrophy, and extracellular matrix (ECM) deposition that would result in LUTS, decreased bladder compliance, residual urine, and even dysfunction of the organ. 4,5 ECM accumulation is of great importance in the progression of BOO that can change the biomechanical properties of the bladder, leading to the transition from compensation to decompensation. 6 Previous studies in chronic obstructive pulmonary diseases (COPD) and asthma, suggested that M receptors played an important role in the process of lung tissue remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Bladder outlet obstruction (BOO) is a urological condition featured by voiding difficulty, abdominal straining during voiding, increased postvoid residual and reduced urine flow rate due to increased detrusor pressure, and which is usually associated with lower urinary tract symptoms (LUTS) (Meier and Padmanabhan, 2016;Niemczyk et al, 2018). The prevalence of BOO was previously predicted to be as high as 21.8% among population aged over 20 years, which is affecting more than one billion patients worldwide (Niemczyk et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Bladder outlet obstruction (BOO) is a urological condition featured by voiding difficulty, abdominal straining during voiding, increased postvoid residual and reduced urine flow rate due to increased detrusor pressure, and which is usually associated with lower urinary tract symptoms (LUTS) (Meier and Padmanabhan, 2016;Niemczyk et al, 2018). The prevalence of BOO was previously predicted to be as high as 21.8% among population aged over 20 years, which is affecting more than one billion patients worldwide (Niemczyk et al, 2018). It is known that BOO pathogenesis could be induced by anatomic factors including benign prostatic obstruction (BPO), pelvic organ prolapses, stricture diseases, urologic malignancies and iatrogenic obstruction, as well as functional causes such as dysfunctional voiding, primary bladder neck obstruction, and Fowler's syndrome (King and Goldman, 2014;Meier and Padmanabhan, 2016;Fusco et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term BOO may result in bladder structure remodeling and bladder detrusor muscle dysfunction, which may in turn lead to a series of urinary tract symptoms, including frequent urination, urination urgency and urinary incontinence, severely compromising the quality of life of the patients ( 2 ). Currently, BOO affects ~1.1 billion individuals worldwide, with the occurrence of BOO and associated lower urinary tract symptoms increasing annually ( 3 , 4 ). During the pathological process of BOO, smooth muscle hypertrophy occurs in an attempt to overcome the increased urethral resistance, which leads to the eventual decompensation to fibrosis ( 5 ).…”
Section: Introductionmentioning
confidence: 99%